Bronchoscopic Cryobiopsy for the Diagnosis of Diffuse Parenchymal Lung Disease - Kropski, Jonathan A.; Pritchett, Jason M.; Mason, Wendi R.; Sivarajan, Lakshmi; Gleaves, Linda A.; Johnson, Joyce E.; Lancaster, Lisa H.; Lawson, William E.; Blackwell, Timothy S.; Steele, Mark P.; Loyd, James E.; Rickman, Otis B. (PloS one, 2013)
Although in some cases clinical and radiographic features may be sufficient to establish a diagnosis of diffuse parenchymal lung disease (DPLD), surgical lung biopsy is frequently required. Recently a new technique for bronchoscopic lung biopsy has been developed using flexible cryo-probes. In this study we describe our clinical experience using bronchoscopic cryobiopsy for diagnosis of diffuse lung disease. A retrospective study of subjects who had undergone bronchoscopic cryobiopsy for evaluation of DPLD at an academic tertiary care center from January 1, 2012 through January 15, 2013 was performed. The procedure was performed using a flexible bronchoscope to acquire biopsies of lung parenchyma. H&E stained biopsies were reviewed by an expert lung pathologist. Twenty-five eligible subjects were identified. With a mean area of 64.2 mm(2), cryobiopsies were larger than that typically encountered with traditional transbronchial forceps biopsy. In 19 of the 25 subjects, a specific diagnosis was obtained. In one additional subject, biopsies demonstrating normal parenchyma were felt sufficient to exclude diffuse lung disease as a cause of dyspnea. The overall diagnostic yield of bronchoscopic cryobiopsy was 80% (20/25). The most frequent diagnosis was usual interstitial pneumonia (UIP) (n = 7). Three of the 25 subjects ultimately required surgical lung biopsy. There were no significant complications. In patients with suspected diffuse parenchymal lung disease, bronchoscopic cryobiopsy is a promising and minimally invasive approach to obtain lung tissue with high diagnostic yield.